(untitled) (Medico Legal Update, 2021)
The current research aims to detect the maternal risk factors that influence the birth weight of the babies. Risk factors related to the mothers like gestational age, maternal age, nutrition, and medical problems play a role in the delivery of infants with low birth weight. The sample consisted of 267 ladies give a birth to newborns. Mothers with less than or = 150cm giving low birth weight babies (62.3%) while those with more than 150cm giving low birth weight babies (37.7%) . In the normal birth weight group, working mothers represent (82.1%) while in normal birth weight group they represent (17.4%). Mothers more than or = 35 years old giving (33.1%) normal birth weight babies. Young mothers less than 20 years old gave more low birth weight babies (28.7%) than older mothers with more 20 years old. The maternal risk factors of low birth weight babies include maternal age < 20 years old, low maternal educational level, working mothers, smoking, pre-pregnancy weight<50kg, maternal height ?150cm, low socioeconomic status, inter pregnancy interval of less than one year, previous low birth weight babies, history of infertility and first week neonatal death, low rate of visiting to antenatal care centers.